2017
DOI: 10.1021/acssuschemeng.7b02380
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles with Surface-Bonded Oxygen for Highly Selective CO2 Reduction

Abstract: The surface electronic structures of catalysts need to be carefully engineered in CO 2 reduction reaction (CO 2 RR), where the hydrogen evolution side reaction usually takes over under a significant overpotential, and thus dramatically lowers the reaction selectivity. Surface oxides can play a critical role in tuning the surface oxidation state of metal catalysts for a proper binding with CO 2 RR reaction intermediates, which may significantly improve the catalytic activity and selectivity. Here, we demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 51 publications
4
43
0
Order By: Relevance
“…It was also reported that structure, morphology, size, and composition of the catalyst can lead to adsorption and decoupling site preferences of different adsorbates of C bound on the surface and further result in the breaking of the linear scaling relationships and tuning of the adsorption strength, eventually exerting a dramatic influence on the ECR performance . Indeed, in addition to polycrystalline and single‐crystalline Ag, some new A types have been developed and characterized recently, such as nanostructured Ag with different sizes, supported Ag catalysts with different substrates including C, TiO 2 , Al 2 O 3 , dopant‐aided Ag, oxide‐derived Ag, and surface‐modified Ag …”
Section: Advances In Ag‐based Co2‐to‐co Electrocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also reported that structure, morphology, size, and composition of the catalyst can lead to adsorption and decoupling site preferences of different adsorbates of C bound on the surface and further result in the breaking of the linear scaling relationships and tuning of the adsorption strength, eventually exerting a dramatic influence on the ECR performance . Indeed, in addition to polycrystalline and single‐crystalline Ag, some new A types have been developed and characterized recently, such as nanostructured Ag with different sizes, supported Ag catalysts with different substrates including C, TiO 2 , Al 2 O 3 , dopant‐aided Ag, oxide‐derived Ag, and surface‐modified Ag …”
Section: Advances In Ag‐based Co2‐to‐co Electrocatalystsmentioning
confidence: 99%
“…In another study, Jiang et al. compared the catalytic activity of Ag NPs pretreated in air (air‐Ag) and H 2 (H 2 ‐Ag) for the selective ECR to CO . As shown in Figure , air‐Ag exhibited a significantly higher CO FE and lower H 2 FE than H 2 –Ag in CO 2 ‐saturated 0.1 m KHCO 3 solution within a potential range of −0.3 to −1.0 V vs. RHE.…”
Section: Advances In Ag‐based Co2‐to‐co Electrocatalystsmentioning
confidence: 99%
“…Typically in literature, the catalysts prepared through such intentional reduction of oxide layers to generate interfaces are commonly known as oxide‐derived (OD) catalysts. This section looks in depth of the various interface/OD catalysts reported in literature …”
Section: Active Sites In Metal‐based Catalystsmentioning
confidence: 99%
“…Electrocatalytic data from refs. Abbreviations: NW, nanowires; NN, nanoneedles, NPs, nanoparticles; EOD, electrodeposited oxide derived; Air‐LC, low concentration; meso, mesoporous. The detailed catalytic activity of these catalysts is presented in Table S2 (Supporting Information).…”
Section: Active Sites In Metal‐based Catalystsmentioning
confidence: 99%
See 1 more Smart Citation